Prevalence of Escherichia coli and Antibiotic-Resistant Bacteria During Fresh Produce Production (Romaine Lettuce) Using Municipal Wastewater Effluents - Summerlin, Harvey N.; Pola, Cícero C.; McLamore, Eric S.; Gentry, Terry; Karthikeyan, Raghupathy; Gomes, Carmen L. (Frontiers in Microbiology, 2021)
High demand for food and water encourages the exploration of new water reuse programs, including treated municipal wastewater usage. However, these sources could contain high contaminant levels posing risks to public health. The objective of this study was to grow and irrigate a leafy green (romaine lettuce) with treated wastewater from a municipal wastewater treatment plant to track Escherichia coli and antibiotic resistant microorganisms through cultivation and post-harvest storage to assess their fate and prevalence. Contamination levels found in the foliage, leachate, and soil were directly (p < 0.05) related to E. coli concentrations in the irrigation water. Wastewater concentrations from 177 to 423 CFU·mL-1 resulted in 15-25% retention in the foliage. Leachate and soil presented means of 231% and 116% retention, respectively. E. coli accumulation on the foliage was observed (p < 0.05) and increased by over 400% during 14-days storage (4 °C). From randomly selected E. coli colonies, in all four biomass types, 81% and 34% showed resistance to ampicillin and cephalothin, respectively. Reclaimed wastewater usage for leafy greens cultivation could pose potential health risks, especially considering the bacteria found have a high probability of being antibiotic resistant. Successful reuse of wastewater in agriculture will depend on appropriate mitigation and management strategies to guarantee an inexpensive, efficient, and safe water supply.